Quality of life among infertile individuals in Malaysia: How do we fair against other Asian countries? - Ariffin, Farnaza; Daud, Suzanna; Zainuddin, Ani Amelia; Ramli, Roszaman; Ismail, Zaliha; Abdul Karim, Abdul Kadir; Abu, Muhd Azrai; Ai Hsing, Fong; Mohd Bustaman, Siti Khadijah; Goh, Pik Pin (2018)
Infertility is defined as failure to conceive following 12- months of regular unprotected sexual intercourse. Infertility problems has been shown to reduce quality of life and can affect a person’s overall health and wellbeing. The Fertility Quality of Life (FertiQoL) questionnaire has been translated into Malay and has been showed to have good properties with consistency in validity and reliability. This is the first study conducted in Malaysia and aims to measure the QoL among infertile individuals and to compare with other Asian countries.